Testosterone Diminishes Cabazitaxel Efficacy and Intratumoral Accumulation in a Prostate Cancer Xenograft Model - Lisanne Mout; Ronald de Wit; Debra Stuurman; Esther Verhoef; Ron Mathijssen; Corrina de Ridder; Martijn Lolkema; Wytske van Weerden (EBioMedicine, 2018)
Inactivation of the androgen receptor (AR) pathway by androgen deprivation therapy (ADT) is the mainstay of (metastatic) prostate cancer therapy. Ultimately, the AR pathway will be re-activated despite castrate levels of circulating androgens. Thereby, maintaining its role even in castration resistant prostate cancer (CRPC). The recent STAMPEDE and CHAARTED trials showed that docetaxel in combination with ADT increased survival in hormone sensitive prostate cancer patients, suggesting cross-talk between AR signaling and chemotherapy efficacy. We hypothesized that a similar interaction may also apply for CRPC that is treated with cabazitaxel. We studied the impact of androgen status on the efficacy, pharmacodynamics and -kinetics of cabazitaxel in a unique and clinically relevant patient derived xenograft model of castration resistant disease. We found that cabazitaxel is highly effective in a castrate setting with strongly reduced AR activation, while tumor growth inhibition by cabazitaxel was completely abolished in the presence of high AR pathway activity. Moreover, additional experiments showed that intratumoral cabazitaxel levels were 3.5 times higher in tumors from castrated mice as compared to tumors from androgen-supplemented animals. We confirmed that cabazitaxel pharmacokinetics were not affected by testosterone, suggesting that androgen status might influence cabazitaxel tumor uptake directly. This study reveals the impact of androgen status on cabazitaxel efficacy and supports the potential of combination of taxane chemotherapeutics with AR axis targeting agents.